Assessing Autosomal InDel Loci With Multiple Insertions or Deletions of Random DNA Sequences in Human Genome - Yao, Yining; Sun, Kuan; Yang, Qinrui; Zhou, Zhihan; Shao, Chengchen; Qian, Xiaoqin; Tang, Qiqun; Xie, Jianhui (Frontiers in Genetics, 2022)
Multiple mutational events of insertion/deletion occurring at or around InDel sites could form multi-allelic InDels and multi-InDels (abbreviated by MM-InDels), while InDels with random DNA sequences could imply a unique mutation event at these loci. In this study, preliminary investigation of MM-InDels with random sequences was conducted using high-throughput phased data from the 1000 Genomes Project. A total of 3,599 multi-allelic InDels and 6,375 multi-InDels were filtered with multiple alleles. A vast majority of obtained MM-InDels (85.59%) present 3 alleles, which implies that only one secondary insertion or deletion mutation event occurred at these loci. More frequent presence of two adjacent InDel loci were observed within 20 bp. The MM-InDels with random sequences present an uneven distribution across the genome and appear a correlation with InDels, SNPs, recombination rate and GC content. The average allelic frequencies and prevalence for multi-allelic InDels and multi-InDels present a similar distribution pattern in populations. Altogether, MM-InDel markers with random sequences can provide useful information for population resolution.